1990
DOI: 10.2527/1990.682562x
|View full text |Cite
|
Sign up to set email alerts
|

Energy utilization in pregnant and lactating sows: modeling of energy requirements.

Abstract: Data on energy metabolism and body composition changes of the pregnant and lactating sow have been considered in order to propose methods for determination of energy requirements according to a factorial approach. Daily requirements for maintenance at thermoneutrality amounts to about 105 and 110 kcal ME/kg BW.75 in pregnant and lactating sows, respectively. During pregnancy, maintenance represents 75 to 85% of the total requirements and is affected greatly by environmental temperature and activity of the anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
155
0
11

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(171 citation statements)
references
References 23 publications
5
155
0
11
Order By: Relevance
“…Previous studies have suggested that sows should gain approximately 45 kg of weight through gestation, 20 kg for the weight of the placenta and other products of conception and 25 kg of maternal body weight gain (Verstegen et al, 1987;Noblet et al, 1990;. In this study, the average sow weight gain was 75 kg (or 36% of body weight) between day 0 and 110.…”
Section: Discussionmentioning
confidence: 64%
“…Previous studies have suggested that sows should gain approximately 45 kg of weight through gestation, 20 kg for the weight of the placenta and other products of conception and 25 kg of maternal body weight gain (Verstegen et al, 1987;Noblet et al, 1990;. In this study, the average sow weight gain was 75 kg (or 36% of body weight) between day 0 and 110.…”
Section: Discussionmentioning
confidence: 64%
“…3 Try/LNAA = tryptophan / LNAA. 4 Tyr/LNAA = tyrosine / (isoleucine + leucine + valine + phenylalanine + tryptophan). T P = 0.09; * P < 0.05; *** P < 0.001.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, sows must mobilize fat and protein reserves [3,4]. The extent of body reserve mobilization depends on the amplitude and the nature of the nutritional deficit.…”
Section: Introductionmentioning
confidence: 99%
“…Primiparous sows generally mobilize body reserves to meet the high energy and nutrient requirements for milk production [1,2].…”
Section: Introductionmentioning
confidence: 99%